Paving the Road to Success: Reflecting Critically on Year One of an Undergraduate Student Support Programme at a large South African university (Journal of Student Affairs in Africa, 2021)
Student success, faculty and university throughput, and the need for adequate and appropriate student support remain prevalent issues in the South African and global higher education sectors. Subsequently, the Faculty of Commerce, Law, and Management at a large South African university applied forTeaching and Development Grant funding in order to address these areas of concern. The grant was awarded and initially intended to help students at risk by implementing appropriate interventions to prevent them from dropping out of university or being excluded. However, being labelled as “at risk”was not well received by students and so the grant holders designed a new programme, adopting a decidedly more holistic approach. As such, the Road to Success Programme was born. The first three months saw those involved conceptualise, plan, and develop strategies, material, and interventionsthat were implemented in January 2015. The vision was to scaffold and support first-year students, particularly those in danger of being academically excluded, through an integrated network of tutorials, workshops, online support, and a series of resources called Toolkits for Success, in an attempt to help students achieve their academic goals. Despite a number of challenges, ranging from funding shortfallsand food security to students’ emotional wellbeing and resilience, 2015 proved invaluable in terms of refining strategies, gaining insight, and programme growth. Preliminary data shows an increased pass rate for students who engaged with the RSP, with higher pass rates linked to greater RSP attendance. Consequently, this article serves as a critical reflection of the RSP at the end of its inaugural year and will share data, highlight lessons learned and challenges faced, and discuss how the programme has been taken to scale in 2016.
Keywords: access with success; higher education; holistic support; pass rate; socio-economic challenges; South Africa; Student success; student support; success programme; throughput